Active labour market policies and job tenure - Cockx, Bart [Verfasser]; Linden, Bruno van der [Verfasser]; Karaa, Adel [Verfasser] (My University, 1998)
"In this paper, we study the effect of subsidised on-the-job training, training for the unemployed and pure wage subsidis on job tenure. Correcting for selection bases, we find that each of the labour market policies increases the length of job tenure. Despite the sensitivity of the estimates to the parametric assumptions with respect to the unobservables, the effect of subsidised on-the-job training schemes is always found to be significantly positive. Training programs for the unemploymed and pure wage subsidies always have a positive, but statistically non-significant effect. Our results provide some support for human capital theories as opposed to matching theories." (author's abstract, IAB-Doku) ((en)) Vergleichende Analyse der Auswirkungen von staatlich geförderter betrieblicher sowie Lohnsubventionen auf die Beschäftigungsdauer der geförderten Personengruppen vor dem Hintergrund theoretischer Erklärungsansätze anhand von belgischen Daten. (IAB)
Keywords: S 5.3 Personalentwicklung; G 1.3.1.2 Weiterbildungsmarkt; L 2.1.3 Erfahrungslernen; L 2.1.1 Informelles Lernen; P 1.7 Benachteiligte; S 2.1.2 Berufsbildungsförderungsgesetz (BerBiFG); G 1.2.2.3 Beschäftigungsformen; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; I 2.2.1 Westeuropa; Betriebliche Weiterbildung; On-the-job training; Berufliche Weiterbildung; Förderung; Arbeitsloser; Lohnsubvention; Beschäftigung; Dauer; Erfolgskontrolle; Quantitative Angaben; Belgien